Balancing the national interest: U.S. national security export controls and global economic competition - Committee on Science, Engineering, and Public Policy (U.S.). Panel on the Impact of National Security Controls on International Technology Transfer (National Academy Press, 1987)
The U.S. national security export controls system--which was instituted to impede Soviet acquisition of high technology from the West--is both necessary and appropriate. Balancing the National Interest provides a thorough analysis of this controls system, examining the current system of laws, regulations, international agreements, and organizations that control the international transfer of technology through industrial channels. Foreign Affairs calls it "the best on the subject to have been published in the 40 years that the United States has exercised controls on exports that might add to Soviet power."